PENERAPAN PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN KEMAMPUAN BERTANYA SISWA KELAS VII-G SMP NEGERI 9 MALANG - Putu Evi Paramithasari Wardana; Tjang Daniel Chandra (Jurnal Kajian Pembelajaran Matematika, 2017)
Based on observations and interviews with Public Junior High School 9 Malang class VII-G mathematics teacher, Ms. DL, it is revealed that class VII-G students were passive in asking questions. They tended to answer predetermined questions asked by the teacher. At the opposite, while asked if they have any questions, the most of the students became silent. If students are unable asking questions, it is impossible to confirm students’ wants, in addition to the lack of students’ participation in the learning process and incapability of teachers to examine students’ level of understanding from objects being learned. Based on presented problems, it is necessary to build a learning environment where students could ask questions according to their cognitive levels. Learning style applied on this research was problem posing. By utilizing the learning style, it is expected that students’ question quality would increase. The purpose of this study is to describe problem posing learning style which has capability in increasing students’ questioning ability via classroom action research. Research subjects selected were 32 Public Junior High School class VII-G students learning perimeter and the area of square. The learning style application resulted in students’ inquiring ability improvement. Based on the data of students’ questioning ability test calculated classically, it revealed 67.5% question quality score in cycle 1 and 78.3% in cycle 2. Relevance of percentage score with learning materials is 91.7% in cycle 1 and 95.7% in cycle 2. The percentage of linguistic score is 68.3% in cycle 1 and 79.4% in cycle 2.